The great slump : capitalism in crisis, 1929-33 - Rees, Goronwy (New York : Harper & Row, Publishers, 1970)
Argues that the problem now is the imbalance between the mountain of financial claims on income and the flow of income. Suggests that the West is likely to experience several more years of slow and erratic growth; and that another major financial crisis within a decade is quite possible .
Includes index
Includes bibliographical references: p. 290-292.
aia 04/05/2018
Loans
Keywords: Depressions; Economic history